Microthrombi Correlates With Infarction and Delayed Neurological Deficits After Subarachnoid Hemorrhage in Mice. Issue 7 (July 2020) - Dienel, Ari; Ammassam Veettil, Remya; Hong, Sung-Ha; Matsumura, Kanako; Kumar T., Peeyush; Yan, Yuanqing; Blackburn, Spiros L.; Ballester, Leomar Y.; Marrelli, Sean P.; McCullough, Louise D.; McBride, Devin W.
Abstract : Background and Purpose: Delayed neurological deficits are a devastating consequence of subarachnoid hemorrhage (SAH), which affects about 30% of surviving patients. Although a very serious concern, delayed deficits are understudied in experimental SAH models; it is not known whether rodents recapitulate the delayed clinical decline seen in SAH patients. We hypothesized that mice with SAH develop delayed functional deficits and that microthrombi and infarction correlate with delayed decline. Methods: Adult C57BL/6J mice of both sexes were subjected to endovascular perforation to induce SAH. Mice were allowed to survive for up to 1 week post-ictus and behavioral performance was assessed daily. Postmortem microthrombi, large artery diameters (to assess vasospasm), and infarct volume were measured. These measures were analyzed for differences between SAH mice that developed delayed deficits and SAH mice that did not get delayed deficits. Correlation analyses were performed to identify which measures correlated with delayed neurological deficits, sex, and infarction. Results: Twenty-three percent of males and 47% of females developed delayed deficits 3 to 6 days post-SAH. Female mice subjected to SAH had a significantly higher incidence of delayed deficits than male mice with SAH. Mice that developed delayed deficits had significantly more microthrombi and larger infarct volumes than SAH mice that did not get delayed deficits. Microthrombi positively correlated with infarct volume, and both microthrombi and infarction correlated with delayed functional deficits. Vasospasm did not correlate with either infarction delayed functional deficits. Conclusions: We discovered that delayed functional deficits occur in mice following SAH. Sex differences were seen in the prevalence of delayed deficits. The mechanism by which microthrombi cause delayed deficits may be via formation of infarcts. Abstract : Supplemental Digital Content is available in the text.